2017
DOI: 10.2147/ott.s137433
|View full text |Cite
|
Sign up to set email alerts
|

Role of downregulated miR-133a-3p expression in bladder cancer: a bioinformatics study

Abstract: It has been discovered that miR-133a-3p acts as a tumor suppressor in bladder cancer (BC). Nevertheless, the function of miR-133a-3p in BC remains unclarified. Thus, we carried out this study to validate the expression of miR-133a-3p in BC and provide insights into the molecular mechanism underlying it. To assess the expression of miR-133a-3p in BC, we searched eligible studies from literature and Gene expression Omnibus (GEO) to perform a meta-analysis. We also plotted the summary receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…We calculated SMD with 95% confidence interval (95%CI) and constructed summarized receiver operating characteristics (SROC) curves following the methods in previous studies [31].…”
Section: Geo Meta-analysis For Mir-30d-5p Expression In Nsclc Tissuesmentioning
confidence: 99%
“…We calculated SMD with 95% confidence interval (95%CI) and constructed summarized receiver operating characteristics (SROC) curves following the methods in previous studies [31].…”
Section: Geo Meta-analysis For Mir-30d-5p Expression In Nsclc Tissuesmentioning
confidence: 99%
“…Although the biological functions of miR-133a-3p remain unclear, miR-133a-3p has been reported to play an anti-tumor role in the development of cancers, including bladder cancer, breast cancer and gastric cancer [12,13,24]. In a study by Huang et al, they reported that miR-133a-3p promotes apoptosis and inhibits cell proliferation and migration in gallbladder carcinoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…TNM, tumor, node, metastasis; b, One-way ANOVA preformed to evaluate distributive feature of miR-204-5p in three or more groups of clinicopathological parameters methods in meta-analyses were identical to those used in previous studies [20,21], and analysis was conducted using by Stata 12.0 (Stata Corp LP, College Station, USA). The role of miR-204-5p in NSCLC diagnosis was studied using receiver operating characteristic (ROC) and summarized receiver operating characteristics (SROC) curves were respectively constructed in accordance with the previous studies [22]. The RT-qPCR data were divided into low-level and high-level groups in according to the median expression level of miR-204-5p(Median = 3.75).…”
Section: Discussionmentioning
confidence: 99%